Passions of the tongue : language devotion in Tamil India, 1891-1970 - Ramaswamy, Sumathi (Studies on the history of society and culture, 1997)
Why would love for their language lead men in southern India to burn themselves alive in its name? This book analyzes the discourses of love, labour, and life that transformed Tamil into an object of such attachment, producing in the process one of modern India's most intense movements for linguistic revival and separatism.